Islamic Politics Configuration after New Order: PKB practice in Probolinggo, Indonesia - Zuhri Humaidi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
After the 1998 reformation era, PKB becomes one of the parties that gained a good reputation. Interestingly, unlike NU in the 1940s to 1970s, when it actively took a part in electoral politics by carrying out the agenda of formalizing Islam, PKB sought to synthesize the value of Islam and Indonesia in the context of a pluralistic state and pay attention to secular issues such as political education. In Probolinggo, the issue of political education became one of the post-reform political issues. This paper aims to formulate political education as designed in PKB's political program, as well as the changing of the political Islam articulation after the reformation. To get accurate data and results, a political sociology approach was used to understand political education within the PKB platform, and to measure the extent to which the ideational formulation is capable of being implemented at the practical and local levels in Probolinggo. The data obtained were analyzed in three contexts; the context of social and political configuration in Probolinggo, the context of political transformation in NU, and the context of the articulation change of post-reform political Islam. The results concluded that PKB political education in Probolinggo faced several constraints, both structural and non-structural, while the relevance was to provide contextualization of the reformation at the national level, marking a shift in NU's political paradigm, as well as the transformation of post-New Order political Islam.